Analysis of the Creation of A. M. Smirnov’s Diptych “Storm on the Sea” (Global Journal of Human-Social Science, 2023)
This article is devoted to the work of the honorary member of the Russian Academy of Arts Alexander Smirnov The purpose of this study is to identify the evolution of the artistic method and language of the specified author based on a comparative analysis of the works written by him on the gospel stories In particular the article draws attention to such works of his as Storm on the Sea and Walking on the Waters as well as some sketches written on the specified topic or close to it in different years and in different styles
Keywords: gospel motifs; gospel images; gospel text in works of fine art; artistic creation; creative method